Injectable hybrid nanofibrous spheres made of PLA and nano-hydroxyapatite for cell delivery and osteogenic induction - Wang, Yawen; Zhang, Xiaopei; Liu, Na; Chen, Renjie; Yu, Chenghao; Yao, Lijie; Chen, Siyu; Yan, Yuying; Wu, Tong; Wang, Yuanfei (Frontiers in Bioengineering and Biotechnology, 2024)
Nanofibrous spheres, with their injectable format and biomimetic three-dimensional topologies that emulate the complexity of natural extracellular environments, have become increasingly attractive for applications in biomedical and regenerative medicine. Our research contributes to this growing field by detailing the design and fabrication of a novel series of polylactic acid/nano-hydroxyapatite (PLA/nHA) hybrid nanofibrous spheres. These advanced structures were created by integrating electrospinning and electrospray techniques, which allowed for precise control over the nanofibrous spheres, especially in size. We have conducted a comprehensive investigation into the nanofibrous spheres' capacity to deliver stem cells efficiently and maintain their viability post-implantation, as well as their potential to induce osteogenic differentiation. The results show that these nanofibrous spheres are biocompatible and injectable, effectively supporting the attachment, growth, and differentiation of bone marrow-derived mesenchymal stem cells while aiding in their targeted transportation to bone defect areas to execute their regenerative functions. The findings of this study could significantly impact the future development of biocompatible materials for a range of therapeutic applications, including bone tissue engineering and regenerative therapy.